A Model Sea Urchin Spicule Matrix Protein, rSpSM50, Is a Hydrogelator That Modifies and Organizes the Mineralization Process - Jain, G.; Pendola, M.; Huang, Y.; Gebauer, Denis; Evans, J. (American Chemical Society, 2017)
In the purple sea urchin Strongylocentrotus purpuratus, the formation and mineralization of fracture-resistant skeletal elements such as the embryonic spicule require the combinatorial participation of numerous spicule matrix proteins such as SpSM50. However, because of its limited abundance and solubility issues, it has been difficult to pursue extensive in vitro biochemical studies of SpSM50 protein and deduce its role in spicule formation and mineralization. To circumvent these problems, we expressed a tag-free bacterial model recombinant spicule matrix protein, rSpSM50. Bioinformatics and biophysical experiments confirm that rSpSM50 is an intrinsically disordered, aggregation-prone C-type lectin-like domain-containing protein that forms dimensionally and internally heterogeneous protein hydrogels that control the in vitro mineralization process in three ways. The hydrogels (1) kinetically stabilize the aqueous calcium carbonate system against nucleation and thermodynamically destabilize the initially formed A CC in bulk solution, (2) promote and organize faceted single-crystal calcite and polycrystalline vaterite nanoparticles, and (3) promote surface texturing of calcite crystals and induce subsurface nanoporosities and channels within both calcite and vaterite crystals. Many of these features are also common to mollusk shell nacre proteins and the sea urchin spicule matrix glycoprotein, SpSM30B/C, and we conclude that rSpSM50 is a spiculogenesis hydrogelator protein that exhibits traits found in other calcium carbonate mineral-modification proteins.